Rethinking Intervention in Environmental Litigation - Carl Tobias (Washington University Law Quarterly, 2000)
Intervention in Public Law Litigation: The Environmental Paradigm (Environmental Paradigm) substantially enhances understanding of intervention in federal environmental disputes. These controversies are a critical type of modern civil lawsuit and perhaps constitute the quintessential form of public law litigation. Professor Peter Appel comprehensively reviews the lengthy history of the intervention mechanism, scrutinizes the substantial 1966 revision of Federal Rule of Civil Procedure 24, and closely examines the phenomenon of public law litigation and intervention in it. Professor Appel, thus, significantly advances the dialogue about public law cases and intervention in them and much that he states is undisputed. Nevertheless, certain aspects of his article are controversial; therefore, Environmental Paradigm warrants a response. This piece undertakes that effort. I essentially afford a friendly critique, which emphasizes several important ways that Professor Appel and I differ and suggests how Professor Appel’s helpful analysis might be elaborated. My thesis is that we need a better understanding of the history, theory, policy, and practice of environmental litigation and of intervention in it. Until our comprehension of these matters is more refined, it will remain difficult to articulate with confidence the best prescriptions for the issues raised by intervention.
Keywords: Citizen suits (Civil procedure); Intervention (Civil procedure); Environmental law; Public law